Provable security 5th international conference, ProvSec 2011, Xi'an, China, October 16-18, 2011 : proceedings - Boyen, Xavier; Chen, Xiaofeng (Lecture notes in computer science, 2011)
This book constitutes the refereed proceedings of the 5th Provable Security Conference held in in Xi'an, China, in October 2011. The 22 full papers presented together with 4 short papers and 2 invited talks were carefully reviewed and selected from 75 submissions. The papers are divided in topical sections on cryptographic primitives; encryption; cryptographic protocols; security models and framework; and key agreement.